(untitled) (Global Journal of Science Frontier Research, 2017)
India is a nation which purely relies on agriculture, so rainfall prediction is very important for agriculture to make crop management decisions. Long scale forecast of rainfall during monsoon season (southwest and northeast), at the spatial firmness of a district, could serve as a significant comment to the agricultural community to take better decisions in yield management. Such forecasts are not producing efficient results which are available now. In this paper rainfall, crops and soil data of Andhra Pradesh (AP)